Spontaneous bleeding from orbital haemangioma in drug-induced thrombocytopaenia. Issue 7 (6th July 2021) - Yen, Chu Yu; Chen, Chun-Chen
Abstract : An 81-year-old woman, a drug-induced thrombocytopaenia (DITP) patient, presented with a case of spontaneous bleeding from an orbital haemangioma manifesting as a sudden onset of ocular pain, proptosis and limited eye movement. Image studies revealed an extraconal, cystic lesion with haemorrhage. The ophthalmopathy was caused by the bleeding of the orbital haemangioma and it was resolved after embolisation of the feeding vessels. Spontaneous bleeding of orbital haemangioma is rare. This case emphasises that DITP may be the cause of spontaneous bleeding of orbital haemangioma by precipitating the inflammatory reactions within the tumour, which further cause the haemodynamic disturbances and ultimate spontaneous bleeding.